2022
DOI: 10.21448/ijsm.1066884
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study on BeeBread: Palynological Analysis, Chemical Composition, Antioxidant and Cytotoxic Activities

Abstract: Bee bread is a bee product obtained as a result of fermentation of pollen stored by honey bees in the cells of the honeycomb. Palynological analysis, chemical composition, antioxidant activity of bee bread and its cytotoxic effect against human lung carcinoma (A549), human prostate cancer (DU 145) and human neuroblastoma (SH-SY5Y) cell lines were investigated in this study. 25 plant taxa were identified with palynological analysis. Fatty acids, cyclic, aromatic, phenolic, terpenoid, diterpen and metallic compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…We found that the BB samples have botanical origins comparable to those found in earlier research on the bee vegetation of Bingöl [21] . Research conducted in the same region has also revealed similar results [18,28] . One of the most significant pollen sources for honeybees is the Trifolium species, as found in this study (BB2) [14,29] .…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…We found that the BB samples have botanical origins comparable to those found in earlier research on the bee vegetation of Bingöl [21] . Research conducted in the same region has also revealed similar results [18,28] . One of the most significant pollen sources for honeybees is the Trifolium species, as found in this study (BB2) [14,29] .…”
Section: Resultssupporting
confidence: 83%
“…[21] Research conducted in the same region has also revealed similar results. [18,28] One of the most significant pollen sources for honeybees is the Trifolium species, as found in this study (BB2). [14,29] Lotus spp.…”
Section: Plant Originsupporting
confidence: 51%
See 1 more Smart Citation
“…Ascorbic acid used as standard at the 50 µg/mL concentration had 89.76 ± 1.00% scavenging activity. According to the findings of Dervişoğlu et al (2022), the ethanolic extract from bee bread exhibited varying degrees of inhibition, ranging from 20.15 ± 0.68% to 93.18 ± 0.44%, depending on the concentration (ranging from 25 to 200 mg/mL). Akhir et al (2017) reported that 70% ethanolic and hexane extract of bee bread exhibited percentage of inhibition 93.60 ± 0.03 and 83.81 ± 0.05, respectively.…”
Section: Discussionmentioning
confidence: 99%